Accuracy of three global positioning systems for determining speed and distance parameters in professional soccer - Schmidt, M.; Nolte, K.; Kolodziej, M.; Ulbricht, A.; Jaitner, T. (15. Symposium der dvs-Sektion "Sportinformatik und Sporttechnologie": Zwischen Geistesakrobatik und praktischer Anwendung: Innovationen in der Sportinformatik und Sporttechnologie - Abstractband, 2024)
Introduction Nowadays, GPS devices are vital in controling training load by calculating total distance covered, distance covered in different speed zones or velocity values, thus allowing decision-making mechanism in professional soccer for sports scientists and coaches. Therefore, the accuracy of the data obtained from GPS devices is crucial, especially when data from different manufacturers are used and compared. Hence, this study investigates the accuracy of three commercial GPS devices (Catapult Sports, STATSports and Kinexon) in determining distances covered with high velocities and maximum velocity during a soccer specific setting in comparison to a 3D-motion capture system.